Corporate Social Responsibility: A Case for the Igbo Trade Apprenticeship System (ITAS) as a Sustainable Model of a Startup Incubator for Social Entrepreneurship in Nigeria, Africa - Chukwuemeka, Ugbaja Solomon (International Journal of Economics, Business and Management Studies, 2019)
One of the current issues in corporate social responsibility is social entrepreneurship, which is seeking social change through an entrepreneurial approach. It is an innovative bottom down economy that seeks to help the community grow economically in a sustainable way that produces economic efficiency. From the findings in this study, there is a significant relationship between the Igbo Trade Apprenticeship System and social entrepreneurship in Nigeria, Africa. It is clear that the Igbo Trade Apprenticeship System as a startup incubator is a sustainable model for corporate social responsibility through social entrepreneurship (social change through entrepreneurial approach). Also, corporate organizations can adopt the Igbo Trade Apprenticeship System (ITAS) as a sustainable model of a startup incubator for social entrepreneurship in their corporate social responsibility projects not only in Nigeria but in other parts of Africa and the world as well. ITAS has already proven to be successful in parts of Nigeria. It has helped the Igbo tribe to survive in the aftermath of the Nigerian-Biafrian war. It helped in reducing the rate of poverty in Igboland by producing wealthy Igbo entrepreneurs and businessmen. It helped apprentices in the skill of business bookkeeping (recording of purchases and sales). It helps in providing for employment job seekers. It also helps in providing apprentices with some funds to start their business, and in handling cultural and legal problems in their businesses by developing in them the cultural intelligence (CQ) for adapting in any given environment and culture.